Molecular Features and Functional Implications of Germline Variants in Triple-Negative Breast Cancer. (5th November 2020) - Ma, Ding; Chen, Si-Yu; Ren, Jin-Xiao; Pei, Yu-Chen; Jiang, Cong-Wei; Zhao, Shen; Xiao, Yi; Xu, Xiao-En; Liu, Guang-Yu; Hu, Xin; Liang, Xiao-Zhen; Yu, Ke-Da; et al.
Abstract: Background: The germline variant spectrum of triple-negative breast cancer (TNBC) is different from that of other subtypes and has demonstrated ethnic differences. However, the germline variants of TNBC among Chinese patients and its clinical significance remain unclear. Methods: Using our multi-omics TNBC cohort (n = 325), we determined the spectrum of germline variants in TNBC and aimed to illustrate their biological and clinical implications. Results: Overall, 16.0% (52 of 325) of TNBC patients harbored at least 1 pathogenic or likely pathogenic germline variant. These germline variants were associated with early onset of TNBC, the occurrence of contralateral breast cancer, the basal-like immune-suppressed mRNA subtype, and the homologous recombination deficiency (HRD) mutation subtype. Somatic allele-specific imbalance was observed in 54.1% of these germline variants, which was correlated with early onset of breast cancer and elevated HRD. The genes BRCA1 (7.4%), RAD51D (2.8%), and BRCA2 (2.2%) were those most frequently mutated. The RAD51D germline variants, especially K91fs, were enriched in Chinese patients with TNBC compared with Caucasian and African American patients. The Chinese-specific RAD51D germline variants were functionally associated with the instability of the RAD51D protein, HRD, and sensitivity to PARP inhibitors. Conclusions: Chinese TNBC patients have a distinct spectrum of germline variants, with a remarkable impact on the clinical and molecular characteristics of the tumor. Integrative germline-somatic analysis may help identify TNBC patients who are most likely to be affected by their germline variants and in performing clinical interventions more precisely. The RAD51D variants enriched in our cohort may serve as therapeutic targets and guide precision treatment of TNBC.